The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1108/09564231011066123
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities for managing service innovation: towards a conceptual framework

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
444
0
24

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 531 publications
(510 citation statements)
references
References 81 publications
9
444
0
24
Order By: Relevance
“…Finally, technology is optional though it plays an important role through interacting with other dimensions as a specific service innovation dimension.. Although Den Hertog et al (2010) conceptually extended their original service innovation model by adding two more dimensions (i.e., new business partner and new revenue model) and introduced a sixdimensional service innovation model, we believe that their original concept of service innovation dimension is more appropriate for developing SIS. Using and validating their extended framework is premature because their original framework has not been empirically validated.…”
Section: Service Innovation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, technology is optional though it plays an important role through interacting with other dimensions as a specific service innovation dimension.. Although Den Hertog et al (2010) conceptually extended their original service innovation model by adding two more dimensions (i.e., new business partner and new revenue model) and introduced a sixdimensional service innovation model, we believe that their original concept of service innovation dimension is more appropriate for developing SIS. Using and validating their extended framework is premature because their original framework has not been empirically validated.…”
Section: Service Innovation Strategymentioning
confidence: 99%
“…Hence, firms adopting SDFS can easily improve the efficiency of their service delivery process to achieve better firm performance. Moreover, the process by which the service provider interacts with their customers could be a source of innovation (Den Hertog et al, 2010). In this case, CIFS concentrates on changes in the depth (customer co-production) and degree (customer contact) by which customers are involved in the service innovation processes.…”
Section: ) Service Innovation Strategies As Intervening Variablesmentioning
confidence: 99%
“…The tension in individual- organization interaction may vary at different stages of innovation process (Lane, Koka & Pathak, 2006). Overall, the process dimension is often implied in these studies, but not studied in depth (e.g., Hertog et al, 2010). The dynamic capabilities literature (e.g., has recently argued that a life-cycle view and a process approach to capability development may enrich organization research Laamanen & Wallin, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Terziovski (2007) on the other hand, suggested just two categories: collaboration and knowledge transfer. Den Hertog et al (2010) identified six dynamic service innovation capabilities (signalling used needs and technological options, conceptualizing, (un)bundling, (co)producing and orchestrating, scaling and stretching, and learning and adapting), arguing for innovation capability as contingent upon the context (i.e. whether the innovation is aiming at product or service improvements).…”
Section: Innovation Capabilitymentioning
confidence: 99%
See 1 more Smart Citation